Physical activity and nutrition program for adults with metabolic syndrome: Process evaluation - Tran, V.; Jancey, Jonine; Lee, Andy; James, Anthony; Howat, Peter; Thi Phuong Mai, L. (2017)
Introduction: The Vietnam Physical Activity and Nutrition (VPAN) program aimed to improve physical activity and nutrition for adults aged 50–65 years with Metabolic Syndrome in Vietnam. The VPAN program consisted of a range of resources and strategies, including an information booklet, resistance band, face-to-face education sessions, and walking groups. This process evaluation assessed the participation, fidelity, satisfaction, and reasons for completing and not-completing the VPAN. Methods: Data were collected by mixed-methods from a sample of 214 intervention participants. Quantitative data were collected via surveys (n = 163); qualitative data via face-to-face exit interviews with intervention program completers (n = 10) and non-completers (n = 10), and brief post education session discussions. Results: Most participants (87%–96%) reported the program resources and strategies useful, assisting them to increase their physical activity level and improving their diet. The education sessions were the most preferred strategy (97%) with high attendance (>78% of participants). The main reasons for withdrawal were work commitments and being too busy. Conclusion: The evaluation indicated that the program reached and engaged the majority of participants throughout the six-month intervention. The combination of printed resources and face-to-face intervention components was a suitable approach to support lifestyle behavioural change in the Vietnamese population.